The antimicrobial and bile acid mediated control of Clostridium difficile infection - Dempster, Andrew William (2018)
Clostridium difficile is an anaerobic, Gram-positive, endospore forming bacillus and is the leading cause of nosocomial infection. Symptoms range from mild diarrhoea to the potentially fatal intestinal complications pseudomembranous colitis and toxic megacolon. The prerequisite for C. difficile infection (CDI) is the perturbation of the healthy microbiota of the gut by broad spectrum antibiotics. It is therefore important to develop therapies which take this in to account, either by minimal disruption of the resident gut microbiota, or by reinstating the protective nature of the gut microbiota. The novel antimicrobial fidaxomicin (FDX) is the first in a new class of macrocyclic antibiotics, with a narrow spectrum of activity for C. difficile. FDX exerts its bactericidal activity by binding to RNA polymerase (RNAP) and inhibiting transcription. The minimum inhibitory concentrations were determined for six clinically relevant isolates of C. difficile and the effect of the drug on spore germination and outgrowth was assessed. Inhibition of C. difficile occurs at low concentrations (0.03 – 0.05 µg/mL) and it was found that FDX does not inhibit the initiation of spore germination, but effectively halts outgrowth at an early stage. The effect of mutations in the β subunit of RNAP were also investigated in terms of susceptibility to FDX and any potential fitness costs incurred to the bacterium. Three separate single nucleotide polymorphisms (SNPs), T3428A, T3428G, G3427T, in the rpoB gene were found to confer reduced susceptibilities to FDX. However, the clinical relevance of these mutations is unclear, as mutants appeared to be attenuated in terms of growth, toxin production and virulence in the hamster model of infection. Clostridium scindens is a member of the healthy gut microbiota and is thought to be a key organism in providing colonisation resistance against C. difficile. C. scindens is the most active transformer of primary bile acids to secondary bile acids, known to inhibit the growth of C. difficile. This occurs due to the gene products of the bile acid inducible operon and a presently unknown reductive arm of the pathway. An RNA extraction protocol for high quality total RNA from C. scindens was developed to aid in the study of the transcriptome of C. scindens cultured with the primary bile acid, cholic acid (CA). This has enabled the identification of potential gene candidates for the reductive arm of the bile transformative pathway of C. scindens. To further study these potential genes, the ability to transfer DNA in to C. scindens is desirable in order to create gene knock outs. The genome of C. scindens ATCC 35704 was assembled and annotated and used to identify potential barriers to DNA transfer. The methylation pattern of this strain identified two type I, twelve type II and one type IV restriction methylation (RM) systems. RM systems were further characterised in an effort to circumvent the RM system barrier to DNA transfer.